An Impedance Matching Network towards Amplifier Design from Conceptual to Practical: Simulation Study. Issue 1 (July 2021) - Yob, R C; Ramli, N H; Bahari, N; Zahid, L; Nasrudin, M W
Abstract: In many systems, the impedance matching networks are vital to ensure their having good performances, especially in such systems performances that related to the gain, linearity, and quality factors. This article mainly focuses on the simulation study of the impedance matching network from conceptual to practical on amplifier design. This simulation study from the conceptual of the ideal transmission-line based design to the practical of the microstrip-line based circuit implemented by using LineCalc of the ADS tool. The gallium nitride high electron mobility (GaN-HEMT) transistor by Cree is being one of the key components in understanding the importance of the impedance matching networks on the amplifier design a t the operating frequency of 5 GHz. The Agilent's Advance Design Systems (ADS) is used to perform this research. The obtained voltage standing wave ratio (VSWR) are approximately to 1 for both conceptual and practical of the impedance matching towards the amplifier design a t5 GHz. Thus, it is showing the maximum power transfer was occurring from the power stages to the load.